2019
DOI: 10.1089/neu.2018.5793
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Mesenchymal Stem Cells Alters Motor Cortex Gene Expression in a Rat Model of Acute Spinal Cord Injury

Abstract: Recent evidence has demonstrated that remote responses in the brain, as well as local responses in the injured spinal cord, can be induced after spinal cord injury (SCI). Intravenous infusion of mesenchymal stem cells (MSCs) has been shown to provide functional improvements in SCI through local therapeutic mechanisms that provide neuroprotection, stabilization of the blood-spinal cord barrier, remyelination, and axonal sprouting. In the present study, we examined the brain response that might be associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Since brain injuries in the chronic phase are heterogenous injuries that are underpinned by numerous complex and interrelated pathophysiological conditions [ 35 ], it is conceivable that the enhanced neural plasticity resulting from MSC injection promotes structural rewiring, which might contribute to functional improvement in chronic state of neural diseases. In addition, there are other multimodal and orchestrated mechanisms, as shown in previous studies [ 3 - 13 , 15 - 18 , 25 , 28 , 32 - 34 , 36 - 38 ]. Given these considerations of the potential therapeutic effects of MSCs in a number of neurological disorders, we planned a clinical trial for chronic brain injury.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Since brain injuries in the chronic phase are heterogenous injuries that are underpinned by numerous complex and interrelated pathophysiological conditions [ 35 ], it is conceivable that the enhanced neural plasticity resulting from MSC injection promotes structural rewiring, which might contribute to functional improvement in chronic state of neural diseases. In addition, there are other multimodal and orchestrated mechanisms, as shown in previous studies [ 3 - 13 , 15 - 18 , 25 , 28 , 32 - 34 , 36 - 38 ]. Given these considerations of the potential therapeutic effects of MSCs in a number of neurological disorders, we planned a clinical trial for chronic brain injury.…”
Section: Discussionmentioning
confidence: 86%
“…The intravenous infusion of MSCs derived from bone marrow improves functional outcomes in experimental animal models of stroke [ 4 - 7 , 9 - 11 ], SCI [ 13 , 14 , 16 , 24 , 30 , 31 ], neonatal hypoxic ischemia [ 12 ], chronic epilepsy [ 17 ], cerebral small vessel disease [ 8 , 32 ], amyotrophic lateral sclerosis [ 33 , 34 ], and peripheral nerve injury [ 18 , 21 ]. Although the mechanisms underlying these beneficial effects have not been fully elucidated, potential mechanisms include neuroprotection and immunomodulation [ 14 ], the induction of axonal sprouting [ 13 ], remyelination [ 13 ], the restoration of the blood-brain and blood–spinal cord barriers [ 13 , 24 ], and the enhancement of remote gene expression responses [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive techniques suited for the clinical application need to be developed. Trials by intravenous injections of MSCs in rodents were widely reported [44][45][46][47][48]. Cultured rat and human MSCs have been shown to migrate into sites of brain injury after cerebral ischemia when transplanted intravenously in rats [49].…”
Section: Discussionmentioning
confidence: 99%
“…No previously reported study has tracked MSCs that were intravenously transplanted into the spinal cord in living animals; to date, only histological assessments have con rmed the fate of stem cells after their systemic transplantation [27,[44][45][46][47][48]. These studies did not evaluate the survival, proliferation, and migration of transplanted cells.…”
Section: Discussionmentioning
confidence: 99%